2015
DOI: 10.1590/0102-311x00119914
|View full text |Cite
|
Sign up to set email alerts
|

Testing the applicability of a model of oral health-related quality of life

Abstract: Resumo O objetivo foi testar as vias diretas e mediadas do modelo de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(55 reference statements)
1
7
0
9
Order By: Relevance
“…Disease-specific HRQL instruments used in the studies included the MacNew Heart Disease Quality of Life [ 24 ], Minnesota Living with Heart Failure Questionnaire (MLFHQ) and the New York Heart Association (NYHA) classification to measure the global HRQL in heart failure [ 23 , 26 , 38 ]. The HIV/AIDS-Targeted Quality of Life (HAT-QoL) instrument [ 29 – 31 ] for HIV/AIDs populations while the Quality of Life, Obesity and Dietetics (QOLOD) [ 18 ], Oral Health Impact Profile (OHIP-14) [ 17 , 33 ] were used in diabetes and oral health populations respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Disease-specific HRQL instruments used in the studies included the MacNew Heart Disease Quality of Life [ 24 ], Minnesota Living with Heart Failure Questionnaire (MLFHQ) and the New York Heart Association (NYHA) classification to measure the global HRQL in heart failure [ 23 , 26 , 38 ]. The HIV/AIDS-Targeted Quality of Life (HAT-QoL) instrument [ 29 – 31 ] for HIV/AIDs populations while the Quality of Life, Obesity and Dietetics (QOLOD) [ 18 ], Oral Health Impact Profile (OHIP-14) [ 17 , 33 ] were used in diabetes and oral health populations respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The association between OHRQoL and dentition status was adjusted for a range of covariates [26, 27], including socio-demographic characteristics (sex, race/skin color, age group (35–39; 40–44 years), household income and education. Although the age range is narrow, we controlled for age-group as there may be subtle differences by age in the association between tooth loss and OHRQoL and previous studies showed differences in prevalence of functional dentition between the ages range 35–39 and 40–44 years old [28, 29].…”
Section: Methodsmentioning
confidence: 99%
“…They resembled the research by Moya, Chappuzeau, Caro and Monsalves (2012), which was performed with elderly individuals. Furthermore, corresponding to this, in the same state, more than half of the elderly had poor perception of their oral health (Santos, 2015).…”
Section: Discussionmentioning
confidence: 73%